2014
DOI: 10.3109/10253890.2014.974030
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a mindfulness stress management program on stress, anxiety, depression and quality of life in women with polycystic ovary syndrome: a randomized controlled trial

Abstract: Polycystic ovary syndrome (PCOS) is a common endocrine disorder with a significant psychological burden throughout the life course of affected women. Thus, use of mindful awareness may be beneficial as an adjunct to conventional medical management of women with PCOS. A randomized, controlled trial was conducted at the Evgenideion Hospital of the Athens University Medical School to explore the impact of an 8-week mindfulness stress management program on measures of depression, anxiety and stress as well as on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 41 publications
5
72
0
Order By: Relevance
“…It is also difficult to make comments on patients' perceptions about their outward appearance since we did not evaluate patient cognitions in this regard. However, recently Stefanaki et al (2015), in an 8 week randomized controlled study found that mindfulness stress management programs seem promising in ameliorating stress, anxiety, depression and improving quality of life. In light of this evidence, we can conclude that patients' cognitive torsions about their appearance could cause or trigger anxiety-depressive symptoms.…”
Section: Discussionmentioning
confidence: 97%
“…It is also difficult to make comments on patients' perceptions about their outward appearance since we did not evaluate patient cognitions in this regard. However, recently Stefanaki et al (2015), in an 8 week randomized controlled study found that mindfulness stress management programs seem promising in ameliorating stress, anxiety, depression and improving quality of life. In light of this evidence, we can conclude that patients' cognitive torsions about their appearance could cause or trigger anxiety-depressive symptoms.…”
Section: Discussionmentioning
confidence: 97%
“…Previous randomized studies with less than 15 infertile women per group have shown potential benefits of MBPs on “perceived stress” (Shahrestani, Qanbari, Nemati, & Rahbardar, ) and “rumination” (Feili, Borjali, Sohrabi, & Farrokhi, ), whereas a more robust study found increased pregnancy rate among women randomly assigned to a mind/body program during their first in vitro fertilization (IVF) treatment (Domar et al, ). Stress measures have also been shown to improve after cognitive behavioral therapy in women with functional hypothalamic amenorrhea (Michopoulos, Mancini, Loucks, & Berga, ) and after a MBP in women with polycystic ovary syndrome (Stefanaki et al, ), two diagnoses that frequently overlap with infertility.…”
Section: Introductionmentioning
confidence: 99%
“…These studies seem to suggest that detection of significant BDNF Val66Met × intervention on reducing anxiety may depend on the intervention targets. Based on the findings in this study that BDNF Val66Met modulates adolescents' susceptibility to stressful life events and mothers' warmth-reasoning, we speculate that the BDNF Val66Met polymorphism may moderate anxious youths' responses to psychotherapies involving stress management such as the mindfulness-based stress reduction (MBSR) program (Hofmann, Sawyer, Witt, & Oh, 2010), which has been found can reduce subjective and physiological (cortisol concentration) stress level, and anxiety symptoms (Stefanaki et al, 2014). The BDNF Val66Met polymorphism may also modulate family-based treatments involving the enhancement of positive maternal parenting such as warmth and inductive-reasoning (Drake & Ginsburg, 2012).…”
Section: Discussionmentioning
confidence: 91%